A Review Of The Rheotanytarsus Curtistylus Group, With A Generic Diagnosis Of The Genus Rheotanytarsus Thienemann Etbause, And A Description Of 7 New Afrotropicalspecies. - Kyerematen, R.A.K. (University of Ghana, 1996)
A revised generic diagnosis of the genus Rheotanytarsus Thienemann et Bause is given. Seven new Afrotropical species are described, R. kjaerandseni sp. n. as male, female, pupa and larva; R. plerusunguisus sp. n. as male and female; R. aquilus sp. n., R. atrius sp. n., R. saetheri sp. n., R* abonae sp. n., and R, weijensis sp. n. as males only. One species is redescribed, R. fuscus (Freeman, 1954). The genus can be divided into 7 species groups primarily based on the pupal morphology: the ceratophylli group, the distinctissimus group, the globosus group, the curtistylus group, the pentapoda group, the nigricauda group, and the reissi group. A phylogenetic treatment using the manual Hennigian method gives the ceratophylli group as the sister group of the remaining groups. The distinctissimus and the globosus groups combined form the sister group of the remaining groups, where as the curtistylus and pentapoda groups combined, and the nigricauda and the reissi groups combined are sister groups. A key to males of the Rheotanytarsus curtistylus group from the Afrotropical region is given. The biology, ecology and distribution of the genus are outlined. Generally, the Ghanaian species of Rheotanytarsus are smaller with lower antennal ratios and lower chaetotaxy than the species from Eastern and Southern Africa and temperate areas. This might be an adaptation to the warm, humid climate in the rainforests of Ghana, whereas the species from Eastern and Southern Africa come from either montane habitats or from localities with a much cooler climate, respectively. The genus apparently is of Pangaeic origin fragmenting into species group following the division into Laurasia and Gondwanaland and subsequent fragmentations of Gondwanaland. More recent speciation may have been caused by climatic changes during the Quaternary period which led to refuges of forest which persisted during the dry and cold periods. The principal core areas were the main centres of forest which survived during the severe arid period around 18,000 BP. Also later events such as the creation of the Dahomey gap may have played a significant role in speciation.
Thesis(MPhil)_University of Ghana,1996.